Can satellite technology bridge the digital divide? - Hegener, Michiel (Technical Centre for Agricultural and Rural Cooperation, 2003)
The big Internet-by-satellite plans of the mid-1990s have been largely replaced by new, relatively efficient technologies, which may lift objections against satellite as a viable connectivity solution.